The lands between conflict in the East European borderlands, 1870-1992 - Prusin, Alexander Victor (Zones of violence., 2010)
'The Lands Between' investigates the causes and dynamics of conflict in the borderlands of Eastern Europe. It looks at these territories as a whole, synthesising narrower national histories into a wider-ranging study that highlights the common factors feeding conflict across the region.